Marine Bacterial Aromatic Polyketides From Host-Dependent Heterologous Expression and Fungal Mode of Cyclization - Huang, Chunshuai; Yang, Chunfang; Zhu, Yiguang; Zhang, Wenjun; Yuan, Chengshan; Zhang, Changsheng (Frontiers in Chemistry, 2018)
The structure diversity of type II polyketide synthases-derived bacterial aromatic polyketides is often enhanced by enzyme controlled or spontaneous cyclizations. Here we report the discovery of bacterial aromatic polyketides generated from 5 different cyclization modes and pathway crosstalk between the host and the heterologous fluostatin biosynthetic gene cluster derived from a marine bacterium. The discovery of new compound SEK43F (2) represents an unusual carbon skeleton resulting from a pathway crosstalk, in which a pyrrole-like moiety derived from the host Streptomyces albus J1074 is fused to an aromatic polyketide SEK43 generated from the heterologous fluostatin type II PKSs. The occurrence of a new congener, fluoquinone (3), highlights a bacterial aromatic polyketide that is exceptionally derived from a characteristic fungal F-mode first-ring cyclization. This study expands our knowledge on the power of bacterial type II PKSs in diversifying aromatic polyketides.